Problematic aspects of modern professional training of pharmacy masters - N. O. Tkachenko; B. Р. Hromovyk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of the research is to analyze the process of professional training of pharmacy master’s in modern realities to identify problematic issues and find ways to solve them.